Reused substrates in soilless culture greenhouse strawberry production - Feng, Qian; Wang, Liu; Pei, Qingyu; Yin, Yilei; Lu, Lu; Pan, Shoujiang; Tian, Jing; Lu, Shaowei; Li, Shao (International Journal of Agricultural and Biological Engineering, 2025)
This study examined the effects of varying reutilization periods of substrate on its physical and chemical properties and the growth and development of strawberries in a greenhouse. The research focused on a specialized substrate formula that had been reused for either two or four years, utilizing the ‘Hongyan’ and ‘Xiangye’ strawberry varieties as test subjects. A range of parameters was assessed, including the substrate’s physical and chemical properties, photosynthetic performance, fruit quality, and strawberry yield. The results indicated that for the ‘Hongyan’ strawberry, the bulk density of the substrate that had been reused for four years was higher than that of the substrate reused for two years. However, there were no significant differences observed in total porosity,aeration porosity,water holding porosity, or air-to-water ratio between the two substrate durations. Additionally, parameters such as soluble solids content, Vitamin C content, total acid content, and fruit yield did not show significant differences for ‘Hongyan’ strawberries. Conversely, for ‘Xiangye’ strawberries, there were no significant differences in the physical properties of the substrates reused for two years versus those reused for four years. Notably, the yield of ‘Xiangye’ strawberries grown in the substrate reused for four years experienced a significant reduction of 26.86% compared to that of the substrate reused for two years (p<0.05). These findings suggest that the impact of different reutilization periods varies among strawberry varieties. The specialized substrate can be effectively reused for certain varieties that exhibit strong adaptability and resistance within a specified timeframe, helping to lower costs and facilitate substrate reutilization. This approach holds considerable practical application and potential for advancement in the realm of strawberry substrate cultivation and production. Keywords: strawberry, reutilization, substrate physical and chemical properties, photosynthetic parameters, quality, yield DOI: 10.25165/j.ijabe.20251803.9050 Citation: Feng Q, Wang L, Pei Q Y, Yin Y L, Lu L, Pan S J, et al. Reused substrates in soilless culture greenhouse strawberry production. Int J Agric & Biol Eng, 2025; 18(3): 44–50.